Detección de la escoliosis en adolescentes según test postural fisioterapéutico. Baños, 2019 - Villavicencio Valdés, Alexis Alberto (2020)
The main objective of this research project is to detect scoliosis in the students of the Oscar Efrén Reyes Educational Unit, through the application of a physiotherapeutic postural evaluation, in which the correct application of the evaluation allowed identifying the pathology, consequently generating statistical data that demonstrated the incidence of scoliosis in the students of the institution aforementioned. Physiotherapeutic postural evaluation is a body evaluation technique that is based on the detailed observation of different specific body segments, in order to detect characteristic asymmetries, present in scoliosis. The research was cross-sectional with a field design in which 42 students previously observed for a period of time participated, they showed similar characteristics in terms of poor postural attitudes, they were evaluated using the visual analog scale of pain intensity, postural test and Adams test. The results were analyzed through the Excel computer tool, in which it was shown that a large number of students evaluated presented some type of painful symptomatology, and through the application of the postural test, it was detected that more than half of the participants had scoliosis, with a slight tendency in the female sex.